2012
DOI: 10.1074/jbc.m111.306902
|View full text |Cite
|
Sign up to set email alerts
|

Mutant Protein A30P α-Synuclein Adopts Wild-type Fibril Structure, Despite Slower Fibrillation Kinetics

Abstract: Background: A30P ␣-synuclein is associated with the familial form of Parkinson disease. Results: The secondary structure and chemical shifts of A30P ␣-synuclein fibrils are in high agreement with wild-type. Conclusion: A30P ␣-synuclein fibrils adopt the same structure as the wild-type. Significance: This work is an important step toward elucidating the association between the early onset Parkinson disease mutants of ␣-synuclein fibrils and Parkinson disease pathology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
72
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(77 citation statements)
references
References 56 publications
(72 reference statements)
3
72
0
Order By: Relevance
“…This approach has been applied in the present study to characterize the effects of five mutational variants, namely A30P, E46K, H50Q, G51D, and A53T, in α-synuclein that are associated with familial Parkinson's disease (14)(15)(16)(17)(18). Our results show that single-amino acid substitutions in the 140-residue chain of α-synuclein not only increase or decrease the overall rate of aggregation, as noted in earlier studies (22)(23)(24)(25)(26)(27)(28)(29)(30) and as reproduced by us (SI Appendix, Fig. S10), but also dramatically affect the relative importance of individual microscopic steps (Fig.…”
Section: Discussionsupporting
confidence: 49%
See 2 more Smart Citations
“…This approach has been applied in the present study to characterize the effects of five mutational variants, namely A30P, E46K, H50Q, G51D, and A53T, in α-synuclein that are associated with familial Parkinson's disease (14)(15)(16)(17)(18). Our results show that single-amino acid substitutions in the 140-residue chain of α-synuclein not only increase or decrease the overall rate of aggregation, as noted in earlier studies (22)(23)(24)(25)(26)(27)(28)(29)(30) and as reproduced by us (SI Appendix, Fig. S10), but also dramatically affect the relative importance of individual microscopic steps (Fig.…”
Section: Discussionsupporting
confidence: 49%
“…The A53T variant is generally considered to accelerate aggregation compared with the WT protein (22), but less agreement exists concerning the effects of the A30P mutation, because this variant has been variously reported to aggregate more slowly (28), more rapidly (23)(24)(25)(26), or with the same rate (22) as the WT protein. Moreover, for the E46K (27) and H50Q (29,30) variants, the aggregation process has been reported to be accelerated compared with WT α-synuclein, but the G51D variant has been reported to aggregate more slowly than the WT protein (31).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The molecular-level polymorphism observed in Aβ40 fibrils has also been observed in ssNMR studies of amyloid fibrils formed by other disease-associated peptides and proteins, including IAPP (Luca et al, 2007), α-syn (Bousset, et al, 2013; Comellas et al, 2011; Heise et al, 2008; Heise et al, 2005; Lemkau et al, 2012), and tau (Andronesi et al, 2008; Daebel et al, 2012; Frost et al, 2009b). Thus, in general, molecular structures within amyloid fibrils formed in vitro are not determined uniquely by the amino acid sequences of amyloid-forming peptides and protein.…”
Section: Molecular Structural Basis For Amyloid Polymorphismmentioning
confidence: 56%
“…This suggests that E46K, H50Q and A53T on one hand and A30P, G51D and WT α-synuclein on the other hand, can give rise to two distinct types of fibrils. It has already been shown that E46K and A53T formed different fibrils compared to WT α-synuclein676869 whereas fibrils of A30P have a similar morphology compared to WT fibrils6970. At the cellular level, differences in fibril morphologies can profoundly affect the biological effect24.…”
Section: Discussionmentioning
confidence: 99%